THE INFLUENCE OF MACROECONOMIC VARIABLES ON THE HUMAN DEVELOPMENT INDEX: EVIDANCE FROM MADURA ISLAND - Budi Prasasti, Karari; Akbar , Taufik; aditama putra mukti wibawa, Wahyu (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
The Human Development Index (HDI) is an important parameter for assessing the extent to which inclusive and equitable development has been achieved, both at the national and regional levels. Madura, an archipelago consisting of four districts, namely Bangakalan, Sampang, Pamekasan, and Sumenep, is an integral part of East Java Province. This study analyzes economic variables, including economic growth, unemployment rates, and poverty, which affect the Human Development Index on Madura Island. The data in this study is panel data from four regencies on Madura Island from 2020 to 2024. The data analysis used in this study is panel analysis. The data used in this study is secondary data sourced from the Central Statistics Agency (BPS). The results of the analysis show that the variables of poverty and unemployment have a significant effect on the Human Development Index variable on Madura Island. Meanwhile, the economic growth variable has no significant effect on the Human Development Index on Madura Island. Therefore, the district governments in Madura must focus more on eradicating poverty and unemployment in order to improve the Human Development Index in their regions